Improving Athletes’ Performance and Avoiding Health Issues - Brito, João; Oliveira, Rafael (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint presents information to update the state-of-the-art knowledge on young, professional or recreational, male and female athletes. Moreover, it addresses current gaps in the literature on issues that have an impact on athletes (e.g., Crohn's disease, Olympic weightlifting, and velocity speed loss). Importantly, this reprint contributes to knowledge on how to improve load monitoring (of training and competition) and health care for athletes through direct or indirect research.